Cold Promoted Activation of Factor VII - Gjønnæss, H (Thrombosis and Haemostasis, 1972)
The activating principle (CPA) of the factor VII activation seen in plasmas of women taking oral contraceptives after overnight incubation of the plasmas at 0° C was investigated. The reaction was dependent on low temperature, and factor XII was indispensable. Concomitant with the activation of factor VII a 10–30 fold increase in TAME esterolytic activity was observed together with a near 100 per cent drop in plasma kininogen concentration. The results indicated that the activation of factor VII is linked to activation of the kallikrein system, and that the activator may be plasma kallikrein.